3D Kanji: A new paradigm of 3D objects to exploit additional dimensions of human sense for enhancing expression. (June 2015) - Yoshioka, Rentaro; Mirenkov, Nikolay; Sekine, Hirotsugu; Noda, Koichi
Abstract: This paper presents "3D Kanji", a new paradigm of 3D objects to enhance human expression by combining the heritage of existing characters and symbols with expressions in 3D space and objects. Expression of thoughts and ideas through 3D objects is a growing area of interest in the emerging era of 3D printing. For an average person, the difficulty lies in modeling and sculpting their ideas into tangible form. 3D Kanji is a new family of 3D objects that can be created and used as people type text today. In this paper, multidisciplinary approaches of applying 3D Kanji objects in various fields and applications are presented. A method to generate such objects is also defined and described. As a further step of development of expression, a method to express emotions using 3D Kanji is presented. An exploratory study to evaluate the feasibility of expressing emotions is presented and results are discussed. Highlights: New paradigm of 3D objects that enhance dimensions of human expression. Method to create 3D objects that highlight features of its original characters/symbols. Systematic approach for expression of ideas and emotion through 3D objects. Cultural heritage built on existing characters can be transformed into 3D objects. Human emotions can be communicated through 3D Kanji objects.